Forensic Assistance in the Investigation of Crimes against Tigers - Georgii G. Omel'yanyuk; Shamil' N. Khaziev; Viktoriya V. Gulevskaya (Теория и практика судебной экспертизы)
The article deals with the problem of providing forensic assistance in the investigation of crimes against tigers, and the work of international organizations and foreign forensic science institutions involved in tiger conservation. It provides information about the key features of tiger anatomy and the formation of tiger tracks and signs in natural habitats, as well as traces left in the event of criminal attacks on animals. Also presented is an overview of forensic trace evidence analysis, as well as forensic ballistics, zoology, veterinary, molecular genetics, and toxicology examinations conducted in order to establish circumstances relevant to the detection, investigation and prosecution of tiger poaching incidents.